Dental, skeletal and soft tissue changes after bimaxillary protrusion treatment with temporary anchorage devices using different retraction mechanics - Kotoe Mayahara; Satoru Kawai; Tomihiro Fujisaki; Noriyoshi Shimizu (BMC, 2024)
Abstract Background Temporary anchorage devices (TADs), which are absolute anchorage, are used for retraction of the anterior teeth in cases of severe bimaxillary protrusion. There have been a number of studies regarding anterior tooth movement using TADs performed by simulation systems and actual treated materials with sliding mechanics. However, there are few studies regarding anterior tooth movement using TADs treated by loop mechanics The purpose of this study was to investigate the effect of TADs in anterior tooth movement using loop mechanics performed in actual cases of bimaxillary protrusion. Methods This study was performed in 20 adult patients with severe bimaxillary protrusion treated with four bicuspid extraction with sliding or loop mechanics (n = 10 in each mechanics) using TADs. The skeletal and denture patterns, as well as the soft tissue profile from pre-treatment (T0) and post-treatment (T1) lateral cephalograms, were compared between sliding and closing loop mechanics. Results The use of TADs is useful for retraction of anterior teeth without molar anchorage loss. in sliding and loop mechanics. The upper anterior teeth were less lingual tipped and lower anterior teeth were more upright resulting in less clockwise rotation of the occlusal plane in loop mechanics compared to sliding mechanics. Conclusion An oblique retraction force vector with a lower point of application causes less intrusion and more lingual tipping of upper anterior teeth as well as more clockwise rotation of the occlusal plane compared to a parallel retraction force vector.